Technical and Economic Analysis of a 1 MWp Solar Power Plant in the Lake Toba Region: Potential and Impact on Green Tourism - Saut M Situmorang; Bonar S,M Naibaho (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
This Lake Toba, one of Indonesia’s most prominent tourist destinations, holds significantpotential to be developed into a sustainable and environmentally friendly tourism area through theintegration of renewable energy. Among the available options, solar energy utilization via SolarPhotovoltaic (PV) systems offers a strategic pathway to achieve energy sustainability and reducereliance on fossil fuels. This study aims to evaluate the solar radiation potential, land requirements,technical design of Solar PV systems, and economic feasibility to support sustainable ecotourismdevelopment in the Lake Toba region. A quantitative research approach was applied, combiningsolar radiation assessment based on Global Horizontal Irradiance (GHI) data from BMKG and theGlobal Solar Atlas with financial feasibility analysis using Levelized Cost of Electricity (LCOE),Net Present Value (NPV), and Payback Period metrics. The results indicate that the Lake Tobaregion receives an average solar radiation of 4.8–5.1 kWh/m²/day, allowing a 1 MWp Solar PVsystem to generate approximately 1.37 GWh of electricity annually. Economically, the systemyields an estimated LCOE of USD 0.056/kWh, significantly lower than diesel-based generationcosts of USD 0.15–0.20/kWh. Environmentally, such a system could reduce carbon emissions byaround 1,163 tons of CO₂ per year, directly supporting Indonesia’s national decarbonization argets. Overall, Solar PV deployment in the Lake Toba region is technically viable, economically competitive, and environmentally impactful, while also strengthening Lake Toba's image as a green tourism destination.